2016
DOI: 10.1542/peds.2015-4571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical, Maternal, and Self Pubertal Assessments: Implications for Health Studies

Abstract: Most epidemiologic studies of puberty have only 1 source of pubertal development information (maternal, self or clinical). Interpretation of results across studies requires data on reliability and validity across sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
2
31
1
1
Order By: Relevance
“…In order to understand the similarities and differences in various assessments of puberty, the correspondence across measures must be understood (Shirtcliff et al, 2009). Cross-sectional studies have generally found moderate correspondence among different measures of self-report (e.g., Brooks-Gunn, Warren, Rosso, & Gargiulo, 1987), and across selfand nurse-reported data on secondary sex characteristics in boys (e.g., Coleman & Coleman, 2002;Jaruratanasirikul, Kreetapirom, Tassanakijpanich, & Sriplung, 2015;Shirtcliff et al, 2009;Terry et al, 2016). Fewer studies have investigated correspondence between nurse-reported secondary sex characteristics and hormone concentrations.…”
Section: Correspondence Among Measuresmentioning
confidence: 99%
“…In order to understand the similarities and differences in various assessments of puberty, the correspondence across measures must be understood (Shirtcliff et al, 2009). Cross-sectional studies have generally found moderate correspondence among different measures of self-report (e.g., Brooks-Gunn, Warren, Rosso, & Gargiulo, 1987), and across selfand nurse-reported data on secondary sex characteristics in boys (e.g., Coleman & Coleman, 2002;Jaruratanasirikul, Kreetapirom, Tassanakijpanich, & Sriplung, 2015;Shirtcliff et al, 2009;Terry et al, 2016). Fewer studies have investigated correspondence between nurse-reported secondary sex characteristics and hormone concentrations.…”
Section: Correspondence Among Measuresmentioning
confidence: 99%
“…Relatedly, the majority of the sample were boys in earlier pubertal stages, and few individuals who had completed puberty were represented; a larger, more heterogeneous sample of boys and girls across pubertal stage is needed for replication. We also relied on parent reports of pubertal status; although parent ratings are shown to correlate with physician ratings of pubertal stage ( Rasmussen et al, 2015 ; Terry et al, 2016 ), research utilizing a more rigorous measure of pubertal status is warranted. Third, although the goal of the study was to focus on youth with ADHD/DBDs, future research should directly compare youth with and without ADHD and assess real world measures of decision making such as ecological momentary assessment, to determine if these laboratory findings generalize to actual adolescent functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Tanner staging has been shown to be a valid measure of pubertal staging and used in previous studies measuring differences across pubertal development ( Braams et al, 2015 ; Goddings et al, 2014 ). Further, parent reports of Tanner stages among pre-adolescents have been shown to correlate with physicians’ ratings of Tanner stages based on physical examination ( Rasmussen et al, 2015 ; Terry et al, 2016 ), suggesting this is an accurate measure of pubertal status. For analyses, we mean-centered Tanner scores within each sex, based on research for sex differences in timing of pubertal development (i.e., females initiate pubertal development at an earlier age than males) ( Marshall and Tanner, 1968 ).…”
Section: Methodsmentioning
confidence: 95%
“…La concordancia y validez de la aplicación de la escala de Tanner en niños y adolescentes por autoevaluación o la evaluación por parte de las madres han arrojado resultados variables (15,16) , con algunos estudios reportando una concordancia interobservador adecuada (15)(16)(17)(18)(19)(20)(21)(22)(23) , mientras otros no recomiendan la autoevaluación como una medida confiable para la determinación del desarrollo puberal (11,15,24) , o reconocen sus limitaciones dependiendo de la variable a identificar, el sexo o el estado puberal (23,27) .…”
Section: Discussionunclassified